Minnesota Tobacco Withdrawal Scale revision 2020, validated Czech translation - Zvolská, Kamila; Štěpánková, Lenka; Pánková, Alexandra; Králíková, Eva (Casopis lekaru ceskych, 2023)
Most smokers are addicted to tobacco or nicotine not only psychosocially but also physically, what results in withdrawal symptoms after they miss their dose. These are one of the major barriers to quitting. In the treatment of tobacco dependence, the evaluation of the degree of withdrawal symptoms helps to guide psychobehavioral intervention and, above all, the choice of the type, dose, and duration of pharmacotherapy. The Minnesota Withdrawal Symptoms Scale is one of the most widely used for this purpose, revised in 2020. We present a validated translation of this update.
Keywords: abstinenční syndrom; Smoking Cessation; tobacco and nicotine dependence; validation; Humans; withdrawal symptoms; Česká republika; Substance Withdrawal Syndrome; lidé; questionnaire; translating; Minnesota; scale; Czech Republic; odvykání kouření